HLA‐A*23:01:19, a novel variant of HLA‐A*23:01, discovered in a West African stem cell transplantation patient. (5th August 2016) - Sidahmed, A. M. Elhassan; Anderson, J.; Stamm, L.; Khan, F.; Berka, N.
Abstract : HLA‐A*23:01:19 differs from HLA‐A*23:01:01 by a single substitution in exon 4.